Multidimensional context awareness in mobile devices - WEI, Zhuo (Institutional Knowledge at Singapore Management University, 2015)
With the increase of mobile computation ability and the development of wireless network transmission technology, mobile devices not only are the important tools of personal life (e.g., education and entertainment), but also emerge as indispensable "secretary" of business activities (e.g., email and phone call). However, since mobile devices could work under complex and dynamic local and network conditions, they are vulnerable to local and remote security attacks. In real applications, different kinds of data protection are required by various local contexts. To provide appropriate protection, we propose a multidimensional context (MContext) scheme to comprehensively model and characterize the scene and activity of mobile users. Further, based on the scheme and RBAC, we also develop a novel access control system. Our experimental results indicate that it achieves promising performance comparing to traditional RBAC (Role-based Access Control).